2018
DOI: 10.1016/j.nano.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Efficient gene editing via non-viral delivery of CRISPR–Cas9 system using polymeric and hybrid microcarriers

Abstract: CRISPR-Cas9 is a revolutionary genome-editing technology that has enormous potential for the treatment of genetic diseases. However, the lack of efficient and safe, non-viral delivery systems has hindered its clinical application. Here, we report on the application of polymeric and hybrid microcarriers, made of degradable polymers such as polypeptides and polysaccharides and modified by silica shell, for delivery of all CRISPR-Cas9 components. We found that these microcarriers mediate more efficient transfecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(80 citation statements)
references
References 45 publications
2
77
0
1
Order By: Relevance
“…The basic principle of polymer carriers' synthesis is comprehensively described in the recent review article [22] and based on so-called layer-by-layer technique, which consists of deposition of oppositely charged polymers onto the sacrificial template [188]. After the dissolution of template, hollow polymer capsules can be produced, which in turn can be loaded with various bioactive compounds, such as drugs [189], nucleic acids [190], macromolecules [9], fluorescent moieties [191], and other. Generally, to impart polymer capsules properties of light sensitivity, their shell should be modified with plasmonic/dielectric NPs.…”
Section: Polymersmentioning
confidence: 99%
“…The basic principle of polymer carriers' synthesis is comprehensively described in the recent review article [22] and based on so-called layer-by-layer technique, which consists of deposition of oppositely charged polymers onto the sacrificial template [188]. After the dissolution of template, hollow polymer capsules can be produced, which in turn can be loaded with various bioactive compounds, such as drugs [189], nucleic acids [190], macromolecules [9], fluorescent moieties [191], and other. Generally, to impart polymer capsules properties of light sensitivity, their shell should be modified with plasmonic/dielectric NPs.…”
Section: Polymersmentioning
confidence: 99%
“…Crosslinked PMA hydrogel and PMA/PLL capsules were used for successful encapsulation and release of siRNA in a reduced environment to target the cancer-related anti-apoptotic factor survinin [195]. DS/Parg microcapsules have also been reported as safe, efficient and non-viral delivery systems for the delivery of CRISPR-Cas9, a gene editing tool for the treatment of various genetic diseases [196]. The internalization of capsules labeled with cyanine-7 into HEK293T-d tomato cells was studied by CLSM and 3D reconstruction images.…”
Section: Delivery Of Nucleic Acidsmentioning
confidence: 99%
“…22 Some studies have confirmed the efficiency of nonviral delivery to be equivalent to that of lentiviral systems, 23 and they represent promising safety and utility of gene editing. 24,25 Nonviral gene delivery could be highly efficient in ex vivo, including that asso-ciated with plasmid DNA and mRNA. 26 CRISPR/Cas9 delivery by the nonviral approach has some advantages and could partly avoid various concerns associated with viral-based delivery.…”
Section: Discussionmentioning
confidence: 99%